Knowledge and Practice of Nurses on Prevention and Management of Intradialytic Hypotension at Kiruddu and Mulago National Referral Hospitals - Shamia Nakabugo; Jacob Twinamatsiko; Loyce Kyarikunda; Philis Chelimo; Daphne Asaasira; Vallence Niyonzima (International Journal of Nephrology and Renovascular Disease, 2025)
Background: Intradialytic hypotension (IDH) remains a significant and distressing complication of hemodialysis, often reducing the efficiency of the dialysis procedure and leading to adverse clinical outcomes. IDH is strongly associated with increased morbidity and mortality rates among hemodialysis patients. This study aimed to evaluate the impact of an educational intervention on nurses’ knowledge and practices regarding the prevention and management of IDH at Kiruddu National Referral Hospital (KNRH) and Mulago National Referral Hospital (MNRH). Methodology: A quasi-experimental study was conducted in the dialysis units of KNRH and MNRH between May and July 2024, involving 25 dialysis nurses. Data were collected using semi-structured questionnaires to assess knowledge and an observation checklist to evaluate practices, both administered pre- and post-intervention. Results: The study recruited 25 nurses with a mean age of 33.1 years, including 13 males. The majority had 1–4 years of dialysis experience. The mean knowledge score significantly increased from 5.3 before the intervention to 13.1 after the intervention (p < 0.05). Similarly, the mean practice score improved from 12 to 20, with the difference also being statistically significant (p < 0.05). Conclusion: The baseline knowledge of nurses was generally low. The educational intervention significantly enhanced nurses’ knowledge and practices in the prevention and management of IDH, highlighting the importance of continuous training to improve patient outcomes in hemodialysis care.
Keywords: Intradialytic hypotension; FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Animal production::Animal nutrition and management; Prevention; Educational intervention; Nurses’ knowledge and practice